Web objects ambient : an integrated platform supporting new kinds of personal web experiences - Firmenich, Sergio Damián; Bosetti, Gabriela Alejandra; Rossi, Gustavo Héctor; Winckler, Marco (2016)
The Personal Web arose to empower end users with the ability to drive and integrate the Web by themselves, according to their own interests. This is usually achieved through Web Augmentation, Mashups, Personal Information Managers (PIM), etc. But despite the diverse approaches, there are still scenarios that require to be solved in combination of more than one of these approaches; this implies the end user knowing more than one tool and being able to coordinate them. This paper presents WOA, a platform conceived under the foundations of the Personal Web, for supporting the collection and materialization of information objects from existing Web content, and their enhancement through the addition of specialized behaviour. This makes it possible to conceive multiple Web information objects coexisting in a same space of information and offering the end user with different modes of interaction, therefore, with multiple kinds of personal Web experiences.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Web Engineering (16ta : 2016 : Lugano, Suiza)
Keywords: SERVICIOS WEB; web personal